2005
DOI: 10.1021/jp053656t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Strategy for Characterization of Essential Dynamical Variables in Oscillatory Systems:  Effect of Double-Layer Capacitance on the Stability of Electrochemical Oscillators

Abstract: An experimentally accessible algorithm for changing the time scale associated with a dynamical variable is proposed. In general, a differential controller can be applied to (a) identify the essential species in oscillatory systems and (b) explore their role in the feedback loops. Here, we report on classifying electrochemical oscillators by changing the time scale over which the electrode potential varies; the type of different electrochemical oscillators is identified based on whether the controlled modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The overall dynamical features are thus consistent with those observed with large (e.g., 1 and 2 mm diameter) electrodes in traditional macrocells. [2, 6, 24, 25, 34-36]…”
Section: Discussionmentioning
confidence: 99%
“…The overall dynamical features are thus consistent with those observed with large (e.g., 1 and 2 mm diameter) electrodes in traditional macrocells. [2, 6, 24, 25, 34-36]…”
Section: Discussionmentioning
confidence: 99%
“…The reaction of those molecules can thus be thought as one of the simplest yet very interesting experimental systems. Of late, Kiss and co-workers [21][22], [23], [24] have discussed the role of temperature and some electrical properties on the oscillation features. For a NDR oscillator, which typically oscillates under potentiostatic control, the authors found theoretically and experimentally that the frequency of oscillations is directly related to the square root of the velocity of charge transfer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these suggestions will be given later in this book, in the discussion of selected experimental oscillatory systems. Here we shall mention that Kiss et al [50] have suggested the application of the method of changing the time scale associated with dynamical variables (see Sect. 2.3) to the classification of the fact that recursive feedback controller can be applied to add (positive or negative) pseudocapacitance to the inherent double layer capacitance of the electrochemical system.…”
Section: Classification Of Electrochemical Oscillators Based On Impedmentioning
confidence: 99%
“…An analogous approach is potentially applicable to CSTR systems, where the inlet concentrations of chemicals could be changed proportional to the concurrently determined time derivative of concentrations [50]. In this way also chemical species essential for the oscillations could be explicitly detected.…”
Section: Classification Of Electrochemical Oscillators Based On Impedmentioning
confidence: 99%